Karakteristik Lambung Kapal Gurindam Fuel Engine Politeknik Negeri Batam - Sapto Wiratno Satoto; Nidia Yuniarsih; Hendra Saputra; Mufti Fathonah Muvariz; Naufal Abdurrahman Prasetyo; Nurman Pamungkas (Politeknik Negeri Batam, 2021)
The character of the ship's hull will determine the speed and movement of the ship. Ship engine power to overcome resistance is influenced by the hull of the ship so that in doing the design it is necessary to calculate precisely. This research is a further study related to the installation of wireless control devices and the design of unmanned hulls but with a different hull and engine shape. The conclusions obtained from this study are the main size of the ship are as follows: LWL = 66.74 cm; B = 32.07 cm; T = 4.91cm; Cb = 0.338. The ship has pre planning at speed: 2.5 - 4.75 knots with 6.09 – 19.6 N resistance and froud number values between 1.028 – 1.952, then experience planning at a speed of 3.5 knots with resistance values starting at 5.59 N with froud number starting at 1.439. To reach the speed of 10 knots, the ship needs around 102 W of power. The object of the ship investigated above is the Batam State Polytechnic Gurindam ship, where the ship was once used for the national fast boat contest in Indonesia. Hopefully with this research, it can provide a knowledge related to the resistance that occur and, in the future, will be used as the basis for the development of the ship to be better designed.